Comparative in vitro antimicrobial effect of Sarcocephalus latifolius (Sm.) E. A. Bruce leaves and roots on foodborne pathogens - Ahoyo, Carlos; Deguenon, Pauline; Dah-Nouvlessounon, Durand; HOUINATO, MARCEL ROMUALD BENJAMIN (My University, 2019)
Sarcocephalus latifolius (Sm.) E. A. Bruce is a plant used traditionally to treat a wide range of infectious diseases, including foodborne ones. This study aimed to compare its roots and leaves extract antibacterial effects in vitro. Thus, these organs were collected, dried and powdered for the extractions and phytochemical screening. Four extracts (water, ethyl-acetate, methanol and ethanol) were tested on ten references strains (RS) and nine non references strains of Staphylococcus isolated from meat strains (MS) using disk method. Minimal inhibitory (MIC) and bactericidal concentrations (MBC) were determined respectively by macrodilution method and by solid culture medium. The results showed that the MS seem more susceptible than RS. The lowest activity was shown by roots hydro-ethanolic extract on Micrococcus luteus, whereas the highest was obtained with leaves ethanolic extract on Staphylococcus cohini. The MIC ranges from 0.312 to 25 mg/ml for the MS and from 6.25 to 12.50 mg/ml for the RS. About MBC, they vary from 12.50 to 50 mg/ml for all susceptible tested microorganisms. S. latifolius extracts have an inhibitory effect on both strains such as Staphylococcus xylosus, Escherichia coli O157, Staphylococcus sciuri, Staphylococcus aureus, M. luteus, Candida albicans, S. cohinii, Proteus mirabilis and bactericidal effect on the three last ones. These results support the traditional use of S. latifolius in infectious diseases control; furthermore, its leaves seem more effective than the roots. These findings may serve as a starting point for the development of a new drug for the control of this kind of diseases and could sustain the species use.
Keywords: Pathogens; medicinal plant; Sarcocephalus latifolius; phytochemical screening; metabolites